The Voice of the Rising Generation : Family Wealth and Wisdom. - Hughes, James E. (Bloomberg., 2014)
Avoid ""Shirtsleeves to Shirtsleeves"" by Finding Your Voice Growing up in a family with significant wealth or a family business can often feel like an exercise in silence. What should you ask? Whom should you ask? When? Is it ever right to talk about such things? The Voice of the Rising Generation speaks directly to those who find themselves living in that silence, the so-called ""next generation."" Great wealth or a family business can act like a ""black hole, "" sapping the dreams and aspirations of future generations who feel that they can never measure up to the fortune''s founder. This bo.